Renal cell carcinoma with widespread metastasis in 19 years old young male – A rare case report. (September 2021) - Ghartimagar, Dilasma; Shrestha, Manish Kiran; Ghosh, Arnab; Ruwanpathirana, Ramitha Eshan; Regmi, Sudeep
Abstract: Introduction and importance: Renal cell carcinoma is the most common malignant tumor of the kidney which occurs more frequently in men and older people than in women and young adults. Renal cell carcinoma is the second most common renal malignancy diagnosed among pediatric and adolescent patients comprising of 2% to 6% of renal cancers. Case presentation: A 19 years old young adult male came with a history of epigastric and back pain, hematuria and weight loss. Per abdominal examination showed a palpable mass in the epigastric and left hypochondriac region. Radiological imaging showed diffuse infiltration of renal interstitium with multiple hypodense lesions in left kidney, renal vein infiltration, and lytic destruction of vertebral bodies and left superior pubic ramus. Fine needle aspiration cytology and trucut biopsy was taken which confirmed renal cell carcinoma, clear cell type with bone metastasis. Clinical discussion: Although most renal cell carcinoma is sporadic and relatively uncommon in young adults, the incidence of renal cell carcinoma in this age group has steadily increased. Young adults are less likely to receive diagnosis of renal cell carcinoma incidentally. A few reported pediatric series have shown that renal cell carcinoma is highly aggressive, tends to be invasive, and metastasizes to the lungs and bones. Conclusion: Young adult with clear cell renal cell carcinoma showing wide spread metastasis is rare. Since, young age is an independent prognostic factor for cancer-specific survival, early diagnosis of the tumor will be beneficial for patients. Highlights: Renal cell carcinoma with wide spread metastasis is rare in young adults. Young adults are more likely to present with symptoms. Symptomatic tumor presentations did not decreased despite modern imaging technique. Younger and generally healthier population rarely come for tumor screening.